Familial hyperphosphatemic tumoral calcinosis: A rare case report from Syria - Balkis Al Abdulrahman; Hiba Eed; Rama Kurdy; Yazan Alwadi; Salwa Alcheikh (Clinical Case Reports)
Key Clinical Message Tumoral calcinosis is a very rare disease mainly caused by a disturbance in phosphate metabolism. It is advisable to contemplate screening more organs such as testes, thyroid, and spleen in patients with TC. This study provides insight into tumoral calcinosis for physicians in the region and encourages future work on the matter. Abstract Familial hyperphosphatemic tumoral calcinosis (FHTC) characterized by progressive deposition of calcium phosphate crystals in soft tissues. Tumoral calcinosis (TC) is often underdiagnosed in Syria as it cannot be confirmed without genetic testing, which is unavailable in Syria. We present the first reported case from Syria of a man with TC. This case has findings that were not reported in other cases such as testicular calcification, brain calcification, enlarged thyroid, and splenomegaly. Determining these genes in the case presented wasn't possible and future studies need to overcome this hurdle.